Experiencing the Analects of Confucius: An experiential game-based learning approach to promoting students' motivation and conception of learning. (July 2017) - Sung, Han-Yu; Hwang, Gwo-Jen; Lin, Chi-Jen; Hong, Ting-Wei
Abstract: The Analects of Confucius is an important course in the curriculum of Asian Studies in the Chinese community and around the world. Students have to learn a collection of the thoughts of Confucius which have shaped world history and the soul of China. However, educators have indicated that most students fail to understand its abstract thoughts, or even realize its spirit in their daily life experience. Meanwhile, with the advancements of technology, learning with computer games is currently a rapidly developing area of interest for researchers, teachers, material writers and application developers in the educational field. Several studies have shown that by properly incorporating learning contents into game scenarios, an experiential game-based learning approach might foster students' motivation to learn through experience. In addition, the experiential game-based approach is a learning method with great potential for motivating students and stimulating their willingness to engage in continuous and constant learning. Thus, in this study, an experiential digital game has been developed and presented to a fifth grade class learning the Analects of Confucius at an elementary school in Taipei city. An experiment was conducted to evaluate the effectiveness of the proposed approach by situating the experimental group in an experiential game-based learning scenario, while the control group learned with a conventional technology-enhanced learning system. The experimental results showed that the proposed approach effectively enhanced the students' learning effects in terms of their learning motivation, deep learning strategy and acceptance of the technology. As a consequence, it is concluded that an experiential digital game-based learning approach can help students understand the conception and meaning of learning, which is important for them to become life-long learners with positive learning attitudes. Highlights: An experiential game-based learning approach is proposed. A digital game is developed to enable students to experience the Analects of Confucius. An experiment was conducted to evaluate the performance of the new approach. The approach improved the students' learning motivation and deep learning strategy. The students highly accepted the new approach.